Calophyllum canum : antibacterial and anticancer plant - Darnis, Deny Susanti; Bakhtiar, M. Taher; Syed Osman Idid, Syed Zahir Idid; Ahmad, Hanad; Sheikh Mohamed , Hassan Ibrahim; Suleiman Ngoto, Shahida (2010)
Human have used plants as a source of medicine throughout the world since time immemorial. Today there are at least 120 distinct chemical substances derived from plants that are considered as important drugs currently in use in one or more countries in the world. In particular, 60% drugs currently in clinical use for treatment of cancer were found to be of natural origin. Calophyllum canum is a large tree which grows in South East Asia and which is popular for its timber. This plant belongs to the family Guttiferae; a family that boasts species which are rich in bioactive phytochemicals. Some species are believed to having medicinal values and are used against several diseases including anti-inflammatory, anti infectious, astringent and antipyretic. We have successfully isolated two compounds from the methanol extract of Calophyllum canum stembarks that active inhibit the growth of Staphylococcus aureus (ATCC 29213 and ATCC 25923). The cytotoxic study on the extracts revealed that the n-hexane extract had the strongest antiproliferation activity, followed by the methanol extract. n-hexane strongly inhibited the growth of TE1 and MCF7 cell lines. IC50 for n-hexane and methanol extract activity on the A549 cell line was found to be 27.96 μg/mL and 78.9 μg/mL respectively.The compounds (CE0 - CE5) isolated from ethyl acetate extract of C. canum are active to inhibit cell proliferation of human cervix adenocarcinoma cells.